A, Analisis Analisis Konstruksi Sosial Citra Program Studi Ilmu Komunikasi Pada Mahasiswa Dalam Memilih Studi di Universitas Islam Syekh Yusuf: Konstruksi sosial citra - Alhaq , Amalia Nur; Mega Nisa , Meidiva; Darmawan , Arya; Aprilianti , Khaerunissa (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2025)
Marketing communication has a central role in establishing relationships between companies and customers, helping in building good brand awareness and maintaining market share. It also helps to improve the company's brand image and values. What's more, understanding the concept of crisis and the importance of communicating in unexpected situations is essential. This can have a major impact on the company's image and performance. Crisis situations, if managed properly, can have a significant positive impact on the company. In this study, the method used is a descriptive method with a qualitative approach. This research aims to describe the actual phenomenon that is happening when the research is carried out and provide a logical interpretation of the phenomenon. This method involves gathering information through interviews and studying documentation, after which analyzing the data using descriptive techniques.